Living better with energy - Programa Alianza en Energía y Ambiente con la Región Andina (AEA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2024)
The Andean region, due to its geography and ecosystem diversity, is highly vulnerable to climate change. Farming communities face significant challenges, especially during severe winters, when crops and food are affected. However, the implementation of renewable technologies such as hot rooms, hot springs and solar panels has brought economic, health and environmental benefits, improving the quality of life and health of families. These innovations have also empowered women and fostered social change. Healthy housing projects and drip-irrigated phytotomes have improved nutrition and reduced chronic malnutrition. In addition, the use of renewable energy has reduced respiratory diseases and improved hygienic conditions in schools. Improved cookstoves have significantly reduced air pollution in homes, improving the health of residents. Biodigesters have promoted the use of biogas, reducing tree felling and providing nutrient-rich organic fertilizer. These projects seek to strengthen local capacities and improve the lives of Andean communities in a sustainable manner.